Using the Emic–Etic Distinction to Understand the Medieval Christian Interpretations of Slavic Pagan Religion - Dynda, Jiří (Method & theory in the study of religion, 2026)
This article experimentally applies anthropological perspectives to ancient European religions, focusing on Slavic pre-Christian beliefs. It aims to offer nuanced analytical tools and a reflective framework to interpret these religions, primarily by examining how Christian sources portray Slavic paganism and discussing the emic-etic distinction’s advantages and limitations. The article categorizes the strategies employed by medieval Christian writers in their writings and summarizes the emic-etic debate in the study of religion and its connection with the insider-outsider debate. In evaluating these sources and the religious systems they describe, the author suggests that both insider and outsider perspectives contain inherent emic and etic aspects. The proposed "acad-etic" position encourages acknowledging modern academic presuppositions that may influence understanding the data. The article underscores the need for a holistic approach, considering historical and social contexts and the discursive strategies used in describing ancient religions.